David Mamet’s Oleanna: A Contravention of University Ethics Through Controversial Defamation - Abed, Hamid Hammad (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims to explore the potential risks associated with lecturer-student interactions in a university setting. It also endeavors to underscore the roles that instructors and students play within the academic environment and how they respond to any potential issues that may arise. Methods: The study adopts a critical approach to analyze Mamet’s Oleanna. It relies on textual analysis of the play, complemented by an interview with the dramatist David Mamet to enhance the understanding of his intentions. The language used by each character, considered a fundamental element, is crucial in unveiling their genuine motivations. Results: The study demonstrates that many significant problems can be identified and effectively managed. It also affirms that the relationship between the professor and the student is inherently contentious unless built on mutual respect and understanding. Ignoring appropriate university ethics may lead to instances like Carol defaming Professor John. Therefore, establishing a calm and secure learning atmosphere, free from improper behavior by some lecturers or students, is deemed the most suitable approach. Conclusions: The study concludes that individuals may intentionally conceal their true intentions to avoid embarrassment. Manipulating goals to justify means is identified as a violation of university ethics. Professor John, instead of violating university ethics like Carol, accepted defamation and humiliation. This emphasizes the importance of maintaining ethical standards in academic settings.